THE EFFECT OF PROGRESSIVE MUSCLE RELAXATION TECHNIQUES ON ANXIETY LEVELS IN PREOPERATIVE PATIENS WITH GENERAL ANESTHESIA TECHNIQUES AT AMANDA CIKARANG SOUTH HOSPITAL - Alvin Arvela; Amelia Wulandari; Neng Imas Susanti (Keperawatan Anestesiologi Program Sarjana Terapan, 2025)
Background: Preoperative anxiety can be defined as a feeling of fear or anxiety characterized by increased heart rate, blood pressure, rapid breathing, chest tightness, and muscle tension. One of the non-pharmacological methods that can help reduce anxiety is the progressive muscle relaxation technique. The purpose of this study was to determine the effect of progressive muscle relaxation techniques on anxiety levels in preoperative patients with general anesthesia techniques. Methods: This study uses quantitative methods with the type of research Quasy experiment with pre and post test without control design. The sampling technique used purposive sampling involving 33 respondents. Data were analyzed using paired t-test. The research instrument was the Amsterdam Preoperative Anxiety And Information Scale (APAIS) questionnaire. Results: The characteristics of respondents were mostly aged 26-35 (33.3%), gender mostly female (66.7%), surgical experience showed the characteristics of respondents mostly had never had surgery (60.6%), and based on the level of anxiety before the progressive muscle relaxation technique was performed more respondents experienced moderate anxiety (48.5%), while after the progressive muscle relaxation technique was performed the results of the respondents anxiety level mostly decreased to mild anxiety (72.7%). Statistical test results show a decrease in anxiety levels after progressive muscle relaxation techniques with a p-value 0.000. Conclusion: It is concluded that there is an effect of progressive muscle relaxation techniques on anxiety levels in preoperative patients with general anesthesia techniques at Amanda Hospital, Cikarang Selatan.